Presencia y esencia de las tradiciones de Ricardo Palma en las tradiciones cuzqueñas de Clorinda Matto de Turner - Paz-Soldán, Rosario Valdivia (2018)
In this article, the main aim is to show how Clorinda Matto de Turner used in her literature the figure of Ricardo Palma and his stylistic prose. I have noted that in most of her work, Turner reflects in Ricardo Palma’s literature and criteria so that she could conveyed smoothly and genuinely the humoristic style and prose to “Tradiciones Cuzqueñas”. Besides, there are some similar topics in her literature as for instance, “Peruvian Independence”, “Customs in Peruvian towns, especially Cuzco in the colonial age”, “The affair among Spanish conquerors and demoiselles”, “Life of religious military kings”, respectively. All of those topics were used to convey Peruvian culture and customs as a whole. Thus, “Tradiciones Cuzqueñas” genuinely conveys how Clorinda Matto de Turner used Ricardo Palma’s rhetoric style to express the culture, customs, aptitudes and symbolism of Cuzco.